SPLAT : A new technique for pink bollworm management in cotton - Acharya, Licon Kumar; Birah, Ajanta; Khokhar, M K (Indian Farming, 2023)
Cotton is one of the most important fibre and cash crop worldwide as well as in India, and called as ‘white gold’. It plays a major role in the industrial and agricultural economy of the country by providing the basic raw material to the textile industry. Cotton in India is cultivated in different soils, climates and agricultural practices, and grown extensively in different states of India i.e., Maharashtra, Gujarat, Karnataka, Madhya Pradesh, Punjab, Rajasthan, Haryana and Tamil Nadu. With the introduction of Bt cotton, while on one hand, important cotton pests such as American bollworm, spotted bollworm and tobacco bollworm have reduced, on the other, many small sucking pests once considered minors have emerged as major pests. The pink bollworm is re-emerging as an important pest on cotton in central and south India as well as in north India, since last 6-7 years. Severity of this pest has increased and become a formidable problem due to its resistance to cryo-toxins and insecticides. Conventional pesticide against pink bollworm is ineffective because of its internal feeding habit coupled with its resistance to major pesticides and Bt toxins. In these paradoxical circumstances, farmers left with no option but to explore the possibility of novel, ecofriendly, long-lasting alternative to manage this pest. A novel mating disruption-based technology called SPLAT (Specialized Pheromone and Lure Application Technology) can be a ray of hope tocurb the menace of pink bollworm.